Childhood Migraine and Infantile Colic - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2013)
Investigators at the Robert Debre Hospital, Paris, and other centers in France and Italy report a case-control study of 208 consecutive children aged 6 to 18 years presenting to the ED and diagnosed with migraine and controls with minor trauma.